Radiographic Imaging in Dentistry: Psychological Implications and Patient-Centered Nursing Approaches - Abdulrahman Saud Alotaibi; Maha Ali Ahmed Al Ghuson; Adil Abdulrahman Alharby; Ahmad Riqaan Alasmary; Bander mohammed awadbedaiwi; Ghamiyah Rubayan Alqahtani; Ghadeer Oudah Awad Alsaidalani; Nawal Ibrahem Ali Alshami; Aissa Mohammed Ahmad Alshahri; Fatmah Mohammed Alhosseni; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Radiographic imaging represents one of the most valuable methods of modern dentistry, enlightening the status of the mouth and teeth in patients. However, this kind of advanced diagnosis is not only important in detecting dental problems; it also significantly influences the psychology of patients in dental treatments. Anxiety and fears of dental treatment can be amplified by the use of radiographs, and hence, dental nurses must be taught patient-centered nursing approaches. Berkovitz et al. (2018) note that an understanding of the psychological effect of radiographic imaging will thereby help dental practitioners offer necessary supportive care and reassure patients emotionally. This can be a positive influence on improving patient experience. Therefore, this introductory part sets the stage for explaining the interface of radiographic technology, psychological well-being, and empathetic care in dental nursing practices. McGowan et al.